Public perception towards the factors that lead to the reduction of poverty rate; a case study at Bandaraya Melaka, Melaka / Aizatul Marsitah Ibrahim and Nur Raihan Dayana Khamis - Ibrahim, Aizatul Marsitah; Khamis, Nur Raihan Dayana (Faculty of Administrative Science and Policy Studies, 2013)
Poverty has been a problem in Malaysia since independence and even before the independence. This situation had started during the colonial era when the British brought in immigrant workers into Malaya. British brought in workers from China to work in the mines and the Indians to work in estates and plantation. Then, they had implemented the Divide and Rule whereby the Chinese will stay in the city doing the businesses and mines sector. While, the Indians stay in the rubber plantations and estates and the Malays stay in the rural areas doing traditional activities for living such as agriculture and livestock. These situations remain until now whereby the Chinese dominated the economy and businesses while the Malays stay in villages and experiencing the poverty. Thegaps between the citizens either among the rural-urban or between the ethnics showed that there are huge income inequalities. This had caused a high rate of poverty in Malaysia. Then, government had highlighted this issue and took a lot of initiatives in order to eradicate the poverty in Malaysia. The initiatives include the formulation of poverty eradication policies and programs such as the New Economic Policy, National Development Policy and Vision 2020. As a result, the poverty rate had decreased either among the states or rural-urban. The decrease of poverty rate can be clearly seen in Melaka as the state had successfully eradicated the hardcore poor. Hence, a study conducted in order to identify the factors that lead to the reducing of poverty rates in Melaka Tengah. The factors identified that lead to the reducing of poverty rates are the poverty eradication programs itself.